2022
DOI: 10.3389/fcvm.2022.813310
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Predictive Values of Circulating Extracellular Vesicle-Carried microRNAs in Ischemic Heart Disease Patients With Type 2 Diabetes Mellitus

Abstract: Ischemic heart disease patients with diabetes mellitus (IHD-DM) have a higher risk of cardiovascular events than those without DM. Rapid identification of IHD-DM can enable early access to medical treatment and reduce the occurrence of cardiovascular adverse events. In the present study, we identified and examined extracellular vesicle (EV)-carried microRNAs (miRNAs) as the possible diagnostic biomarkers of IHD-DM. Small RNA sequencing was performed to analyze the EV-carried miRNAs spectrum, and differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A small study investigated the expression of miR-210 in plasma-derived extracellular vesicles in T2DM patients with ischemic heart disease. They reported a downregulation of miR-210 compared to healthy controls and concluded that plasma-derived extracellular vesicles and their cargo could be a potential biomarker for ischemic heart disease in T2DM [ 86 ]. Zhu and Leung concluded that miR-221 is significantly upregulated in the serum of T2DM patients and is one of the most important biomarkers for T2DM [ 71 ].…”
Section: The Role Of Micrornas In Atherosclerosis Psoriasis T2dm and Ramentioning
confidence: 99%
“…A small study investigated the expression of miR-210 in plasma-derived extracellular vesicles in T2DM patients with ischemic heart disease. They reported a downregulation of miR-210 compared to healthy controls and concluded that plasma-derived extracellular vesicles and their cargo could be a potential biomarker for ischemic heart disease in T2DM [ 86 ]. Zhu and Leung concluded that miR-221 is significantly upregulated in the serum of T2DM patients and is one of the most important biomarkers for T2DM [ 71 ].…”
Section: The Role Of Micrornas In Atherosclerosis Psoriasis T2dm and Ramentioning
confidence: 99%
“…A small study investigated the expression of miR-210 in plasma-derived extracellular vesicles in T2DM patients with ischemic heart disease. They reported a downregulation of miR-210 compared to healthy controls and concluded that plasma-derived extracellular vesicles and their cargo could be a potential biomarker for ischemic heart disease in T2DM [77]. Zhu and Leung concluded that miR-221 is significantly upregulated in the serum of T2DM patients and is one of the most important biomarkers for T2DM [62].…”
Section: Mir-210mentioning
confidence: 99%
“…Another inflammation-associated miR that downregulates the MR is miR-155-5p. Reduced blood levels of miR-155-5p were not only found in patients with coronary artery disease with intermittent hypoxic states for cardiomyocytes, but also in patients with diabetes mellitus and ischemic heart disease [ 179 , 180 , 181 ]. Additionally, age was inversely correlated to miR-155-5p blood levels [ 179 ].…”
Section: Mr Signaling and Micromilieumentioning
confidence: 99%